Decentralisation law and economic development: discussing the opportunities and constraints in the promotion of small scale investments in Cameroon (African Journal of Law and Politics, 2023)
Cameroon’s incessant quest to promote investment and especially small scale investments dates back to the enactment of the investment charter in 2002. This zeal of the state was re-echoed in the decentralisation laws of 2004 as consolidated by the General Code of Regional and Local Authorities enacted in 2019. These laws conferred on decentralised authorities a preponderant role in the development of small enterprises, opening opportunities to that effect. However, since 2004, little or no progress has been recorded by decentralised local authorities in the promotion of small scale investments, especially at the local level, due to several constraints. This puts to question the potential of these authorities to achieve this daunting task. This paper examines the perspectives on the promotion of the development of small scale investments by decentralised authorities in Cameroon and the challenges encountered. Through qualitative research, the article critically examines efforts made so far and reveals that decentralised authorities are yet to fully engage in the development of small scale investments. It is on this basis that policy recommendations are made, advising the councils most especially, to broaden their revenue base and the State to accelerate the process of decentralisation in Cameroon.